The Clinical Significance of O6-Methylguanine-DNA Methyltransferase Promoter Methylation Status in Adult Patients With Glioblastoma: A Meta-analysis - Zhao, Yu-Hang; Wang, Ze-Fen; Cao, Chang-Jun; Weng, Hong; Xu, Cheng-Shi; Li, Kai; Li, Jie-Li; Lan, Jing; Zeng, Xian-Tao; Li, Zhi-Qiang (Frontiers in Neurology, 2018)
Background and Objective: Promoter status of O6-methylguanine-DNAmethyltransferase (MGMT) has been widely established as a clinically relevant factor in glioblastoma (GBM) patients. However, in addition to varied therapy schedule, the prognosis of GBM patients is also affected by variations of age, race, primary or recurrent tumor. This study comprehensively investigated the association between MGMT promoter status and prognosis in overall GBM patients and in different GBM subtype including new diagnosed patients, recurrent patients and elderly patients. Methods: A comprehensive search was performed using PubMed, EMBASE, Cochrane databases to identify literatures (published from January 1, 2005 to April 1, 2017) that evaluated the associations between MGMT promoter methylation and prognosis of GBM patients. Results: Totally, sixty-six studies including 7886 patients met the inclusion criteria. Overall GBM patients with a methylated status of MGMT receiving TMZ-containing treatment had better OS and PFS (OS: HR=0.46, 95%CI: 0.41-0.52, p<0.001, Bon=0.017; PFS: HR=0.48, 95%CI: 0.40-0.57, p<0.001, Bon=0.014), but no significant advantage on OS or PFS in GBM patients with TMZ-free treatment was observed (OS: HR=0.97, 95%CI: 0.91-1.03, p=0.08, Bon=1; PFS: HR=0.76, 95%CI: 0.57-1.02, p=0.068, Bon=0.748). These different impacts of MGMT status on OS were similar in newly diagnosed GBM patients, elderly GBM patients and recurrent GBM. Among patients receiving TMZ-free treatment, survival benefit in Asian patients was not observed anymore after Bonferroni correction (Asian OS: HR=0.78, 95%CI 0.64-0.95, p=0.02, Bon=0.24, I2=0%; PFS: HR=0.69, 95%CI 0.50-0.94, p=0.02, Bon=0.24). No benefit was observed in Caucasian receiving TMZ-free therapy regardless of Bonferroni adjustment. Conclusions: The meta-analysis highlights the universal predictive value of MGMT methylation in newly diagnosed GBM patients, elderly GBM patients and recurrent GBM patients. For elderly methylated GBM patients, TMZ alone therapy might be a more suitable option than radiotherapy alone therapy. Future clinical trials should be designed in order to optimize therapeutics in different GBM subpopulation.